Power law scaling and country-level centralization of global agricultural production and trade. (1st March 2022) - Dupas, Marie-Cécile; Halloy, José; Chatzimpiros, Petros
Abstract: Global food production and international trade are rapidly expanding and drive increasing agricultural globalization and specialization. Following production patterns, network properties and added-value chains, exportable surpluses of countries can offset food and feed deficits in other countries. However, production and trade patterns are barely addressed in the scientific literature as two interactive components of global agriculture. Integrated analysis of the temporal dynamics and distribution patterns of production and trade among countries can help addressing future food security challenges in view of ongoing trends. Here, we analyse the interdependent patterns of global agricultural production and trade from 1986 to 2016. We classify total production and trade mass into six product categories—cereals, oilcrops, meat, fruits and vegetables, coffee and cocoa. We estimate reexports in global trade by assessing mass balances of production, imports and exports per country. We show that global trade and reexports increase exponentially faster than production and that production and trade are highly centralized among a small number of countries. For most agricultural categories, the centralization of flows has increased in time for production and net exports, and has decreased for net imports and reexports. Accordingly, a growing number of deficient countries are sustained by a decreasing number of top-producing countries. In parallel, reexport routes are increasingly dominated by long-industrialized countries besides the increase in time in the number of reexporting countries. We discuss the interdependencies between global agricultural production and trade patterns. We highlight the drivers and implications of the observed trends for food security challenges.